The Co-produced Pathway to Impact Describes Knowledge Mobilization Processes - David Phipps; Joanne Cummins; Debra J. Pepler; Wendy Craig; Shelley Cardinal (The University of Alabama, 2022)
Knowledge mobilization supports research collaborations between university and community partners which can maximize the impacts of research beyond the academy; however, models of knowledge mobilization are complex and create challenges for monitoring research impacts. This inability to sufficiently evaluate is particularly problematic for large collaborative research networks involving multiple partners and research institutions. The Co-produced Pathway to Impact simplifies many of the complex models of knowledge mobilization. It is a logic model based framework for mapping the progress of research -> dissemination -> uptake -> implementation -> impact. This framework is illustrated using collaborative research projects from Promoting Relationships and Eliminating Violence Network (PREVNet), a pan-Canadian community-university network engaging in knowledge mobilization to promote healthy relationships among children and youth and prevent bullying. The Co-produced Pathway to Impact illustrates that research impact occurs when university researchers collaborate with non-academic partners who produce the products, policies, and services that have impacts on the lives of end beneficiaries. Research impact is therefore measured at the level of non-academic partners and identified by surveying research partners to create narrative case studies of research impact.